2000
DOI: 10.1074/jbc.m003023200
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Transcription of Biphenyl Catabolic bphOperon in Pseudomonas pseudoalcaligenes KF707

Abstract: Pseudomonas pseudoalcaligenes KF707 possesses a chromosomally encoded bph gene cluster responsible for the catabolism of biphenyl/polychlorinated biphenyls. The gene cluster consists of (orf0)bphA1A-2(orf3)bphA3A4BCX0X1X2X3D. We studied the role of orf0 and transcription in the KF707 bph operon. Primer extension analyses revealed that at least as many as six transcriptional initiation sites exist upstream of orf0, bphA1, bphX0, bphX1, and bphD, including two upstream of bphD. The orf0-disruptant failed to grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 34 publications
2
63
1
Order By: Relevance
“…The deduced gene product of ORF3A2-14, which was located upstream of dmpCDEFGH, is 43% identical to the Orf0 protein, a GntR-type transcriptional Aromatic catabolic pathways in microbial community H Suenaga et al regulator of the biphenyl-catabolizing (bph) operon of P. pseudoalcaligenes KF707 (Watanabe et al, 2000). Fosmid types 3A2 and 2C5 differ remarkably in that the two dmp gene clusters in 3A2 are separated by an intervening 10-kb sequence that does not appear to be involved in the degradation of aromatic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The deduced gene product of ORF3A2-14, which was located upstream of dmpCDEFGH, is 43% identical to the Orf0 protein, a GntR-type transcriptional Aromatic catabolic pathways in microbial community H Suenaga et al regulator of the biphenyl-catabolizing (bph) operon of P. pseudoalcaligenes KF707 (Watanabe et al, 2000). Fosmid types 3A2 and 2C5 differ remarkably in that the two dmp gene clusters in 3A2 are separated by an intervening 10-kb sequence that does not appear to be involved in the degradation of aromatic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…It is the case for TraR (44,76), 5 Found on the Web at sanger.ac.uk/Projects/Scoelicolor/. AphS and BphS (18,19), and FucR (51), which bind boxes with no clearly defined symmetrical properties. Thus, although the consensus sequences presented in Table II should be regarded as interesting tools, for instance, in making sequencing projects maximally useful, they certainly should not be considered as unerring references, and some GntR regulators should not fit with the general properties highlighted in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The translation product of orf0 is 58% similar to BphS, a GntR-like negative regulator of bph genes in Ralstonia eutropha A5 (37). Recently, other investigators found that in the PCB degrader Pseudomonas pseudoalcaligenes KF707 the translation product of orf0 is autoregulated and is necessary for expression of genes encoding enzymes in the biphenyl degradation pathway downstream of bphC (48). Induction of genes downstream of bphC allows cells to grow on biphenyl and minimizes the accumulation of metabolites resulting from biphenyl and PCB catabolism.…”
Section: Fig 2 Construction Of a Selectable Lacz Reporter Cassette mentioning
confidence: 99%